When luxury goes digital: does digital marketing moderate multi-level luxury values and consumer luxury brand-related behavior? - Shahzad Ahmad Khan; Ibrahim Rashid Al Shamsi; Taufiq Hail Ghila; Mahwish Anjam (Cogent Business & Management, 2022)
The trajectory of digital marketing has proven to be a powerful medium for customer interaction that offers a unique, exclusive, emotional, and multichannel experience. Brands providing the right value and experience at the right time using the right technology are ought to be successful in winning the customers and outperforming competitors, and luxury brands are no exception. Although the consumer psychology of luxury brands delves deep into the consumer's perception, emotional value, and brand attachment, however, the influx of widespread digitization has changed the way consumers behave and the way the brands engage with the customers. Therefore, this study is an effort to explore the moderating impact of digital marketing on the relationship between the dimensions of luxury value (functional, individual, and social) and consumer luxury brand-related behavior. Following the survey-based data collection approach, a total of 214 workable responses were collected from the consumers of the luxury brands, located in north-eastern and central cities (Rawalpindi, Islamabad, Faisalabad and Lahore) of Pakistan. The research results advocate the significant moderating influence of digital marketing on luxury value and consumer luxury brand-related behavior. Interestingly, the findings also revealed a substantial moderation of digital marketing on the insignificant relationship between the functional value and the consumer luxury brand-related behavior. The study contributes to the literature of digital luxury and consumer luxury brand-related behavior and provides critical insights to the marketers of luxury brands to effectively build brand perceptions while adapting to the digital transformation of luxury brands.
Keywords: 650; Luxury brands; consumer luxury brand-related behavior; digital luxury; functional luxury value; individual luxury value; social luxury value